English Teacher Strategies in Teaching English to Support the Merdeka Belajar Curriculum (MBKM ): A Descriptive Qualitative Study at SMA Negeri 13 Makassar - Rasnawati Abd. Rahman; Sukmawati; Hasnani (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This study aims to describe the strategies used by English teachers in supporting the Merdeka Belajar Curriculum at SMA Negeri 13 Makassar. The Merdeka Belajar Curriculum emphasizes flexible and student-centered learning, adapting learning processes to individual student needs.This study uses a descriptive qualitative method. The subjects of the research were two English teaching at SMA Negeri 13 Makassar. Data were collected through classroom observations and semi structured interviews. Data analysis techniques used include data presentation, conclusion drawing, and trigulation to ensure data validity. The resualt showed that English teachers implemented three main strategies in the learning process, namely cooperative learning, differentiated learning, and problem based learning ( PBL ). Cooperative learning was used to enhance collaboration among students in speaking tasks. Differentiated learning were applied by adjusting the material and method based on students’ abilities and learning styles. Meanwhile, PBL was implemented by assigning challenging tasks that required students to solve problems and present solution independently and actively. In conclusion , the strategies used by English teachers align with the principles of the Merdeka Curriculum, namely meaningful learning , students-centeredneess, and providing space for student potential and learning independence.